2003
DOI: 10.1258/002221503321192430
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial aetiology of non-resolving otitis media in South African children

Abstract: Little is known of the aetiology, serotypes or susceptibility of the pathogens causing non-resolving otitis media in children receiving care from specialists in private practice in developed or in developing countries. Increased access to antibiotics in the community amongst children receiving such private care in South Africa may be anticipated to lead to levels of resistance similar to those found in countries with similar models of private practice, such as the United States. This study was conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
13
1
1
Order By: Relevance
“…Moreover, it wasn't found on nasopharyngeal swabs. In South Africa and Nigeria, prevalence of this bacterium was less frequent with 5.2% and 7.4%, respectively [12,15].…”
Section: Bacteriological Datamentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, it wasn't found on nasopharyngeal swabs. In South Africa and Nigeria, prevalence of this bacterium was less frequent with 5.2% and 7.4%, respectively [12,15].…”
Section: Bacteriological Datamentioning
confidence: 96%
“…In our study, S. pneumoniae come in the second position with 21%. In South Africa, Brazil and France, this bacterium was in first position with a rate of 20.2%, 39.1% and 40%, respectively [12][13][14]. But in Nigeria, the most common agent was Staphylococcus, followed by S. pneumoniae with 8.8% [15].…”
Section: Bacteriological Datamentioning
confidence: 99%
“…5 For S. pneumoniae, the most common pathogen causing otitis media and acute sinusitis, resistance to β-lactam antibiotics can be overcome by increasing dosage. For example, a higher dose of amoxycillin of 90 mg/kg/day is generally recommended for treatment of AOM.…”
Section: Methodmentioning
confidence: 99%
“…Streptococcus pneumoniae was responsible for 8.8% cases of otitis media among children in Ile-Ife (Ako-Nai, 2002), 4.6 % conjunctivitis among children in Ibadan (Adeyeba et al, 2010), 7.5% cases of bacterial infections in children in Abuja (Onalo et al, 2011). In South Africa, 74.5% (35 children out of 47) children with otitis media were due to Streptococcus pneumoniae (Huebner et al, 2003). Several studies have examined household transmission of Streptococcus pneumoniae; most of such studies have suggested that children were the source of transmission to adults in the family (Hoshino et al, 2002;Shimada et al, 2002, Leino et al, 2001.…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 1573-1579mentioning
confidence: 99%